2000
DOI: 10.1542/peds.106.5.e64
|View full text |Cite
|
Sign up to set email alerts
|

Snoring in Portuguese Primary School Children

Abstract: ABSTRACT. Objective. To determine the prevalence of snoring and its potential associations with sleep problems, such as daytime symptoms, medical conditions, school performance, and behavioral disturbances in Portuguese children attending primary school.Methods. A previously validated questionnaire was sent to the parents of 1381 children attending primary schools in a parish of Coimbra, Portugal. To assess behavioral disturbances, the Portuguese version of Rutter's Children's Behavior Questionnaire for comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
3
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 21 publications
7
108
3
11
Order By: Relevance
“…Adenotonsillar disease is seen more commonly in low socioeconomic strata. 9 Present study also revealed that majority of cases (17 cases) belonged to the lower class. We found that children from middle class accounted for 15 cases.…”
Section: Discussionsupporting
confidence: 62%
“…Adenotonsillar disease is seen more commonly in low socioeconomic strata. 9 Present study also revealed that majority of cases (17 cases) belonged to the lower class. We found that children from middle class accounted for 15 cases.…”
Section: Discussionsupporting
confidence: 62%
“…The estimated prevalence of snoring in children is 3 to 12 percent, while OSA affects 1 to 10 percent. [1][2][3] The majority of these children have mild symptoms, and many outgrow the condition. OSA often results from adenotonsillar hypertrophy, neuromuscular disease, and craniofacial abnormalities.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…A previous paper gives full details of methods, which will be summarized here. 12 All 10 schools located in a parish of the city of Coimbra agreed to participate after explaining the aims of the project to all teachers involved in the study. This particular parish was selected because it is the most populous in the city and is considered representative of all social-cultural and economic groups.…”
Section: Subjects and Proceduresmentioning
confidence: 99%